Construction of an in‐house allelic ladder for Canine Genotypes™ Panel 2.1 Kit. Issue 6 (23rd July 2021) - Lee, Minji; Hwang, In Kwan; Jung, Ju Yeon; Kim, Joo‐Young; Chang, Miwha; Moon, Seohyun
Abstract: Dogs ( Canis lupus familiaris ) are among the most common companion animals in the Republic of Korea. Recently, there have been many criminal cases of dog cruelty, injury, and theft, among others. This has increased the importance of dog‐related biological evidence at crime scenes. The National Forensic Service of the Republic of Korea conducts short tandem repeat (STR) analysis using the Thermo Scientific Canine Genotypes™ Panel 2.1 Kit (Canine Kit) to identify individual dogs through forensic analysis. The Canine Kit was developed as a forensic STR kit for the identification of individual dogs. However, an allelic ladder was neither developed nor included in the commercial kit, leaving an issue of accurate genotyping. Primer details for the 18 markers used in the Canine Kit are proprietary information, and thus, unavailable to end‐users. In this study, an allelic ladder was constructed with 160 fragments by combining 158 fragments of STR alleles obtained by nested PCR and two fragments artificially obtained from the sex‐determination marker. By including the new allelic ladder in analysis of samples amplified with the Canine Kit, the accuracy and reliability of data analysis were improved. Application of this allelic ladder would be helpful for interlaboratory data sharing and standardization of canine genotype databases.